2007
DOI: 10.1056/nejmoa073679
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Caffeine Therapy for Apnea of Prematurity

Abstract: Caffeine therapy for apnea of prematurity improves the rate of survival without neurodevelopmental disability at 18 to 21 months in infants with very low birth weight. (ClinicalTrials.gov number, NCT00182312 [ClinicalTrials.gov].).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
518
5
25

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 841 publications
(558 citation statements)
references
References 23 publications
10
518
5
25
Order By: Relevance
“…[76][77][78] As a result of these findings there were concerns about the long-term effects of caffeine on brain development. However, results of placebo-controlled multicenter trials showed that caffeine therapy for AOP reduces the incidence of bronchopulmonary dysplasia 79 and improves survival without neurodevelopmental disability in very low birth weight infants. 80 In this regard, the finding of Back et al 81 that caffeine has a protective effect on chronic hypoxia-induced white matter injury is intriguing.…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…[76][77][78] As a result of these findings there were concerns about the long-term effects of caffeine on brain development. However, results of placebo-controlled multicenter trials showed that caffeine therapy for AOP reduces the incidence of bronchopulmonary dysplasia 79 and improves survival without neurodevelopmental disability in very low birth weight infants. 80 In this regard, the finding of Back et al 81 that caffeine has a protective effect on chronic hypoxia-induced white matter injury is intriguing.…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…The PK profile of caffeine in neonates is characterized by a volume of distribution of 0.8-0.9 L/kg, which is larger than that of children or adults 4,5) . In addition, the half-life of caffeine in neonates is approximately 72-96 hours, which is longer than that of adults, and is further prolonged with decreased renal function.…”
Section: Introductionmentioning
confidence: 97%
“…A recent study demonstrated that caffeine therapy for very preterm infants is associated with significant reductions in the duration of assisted ventilation, the incidence of patent DA, and the rate of bronchopulmonary dysplasia, by ~10%, and that it reduces the incidence of cerebral palsy as compared with placebo-treated infants (18,19). Although these are very important outcomes, the mechanisms responsible are unknown.…”
mentioning
confidence: 99%